Superb exposure of a channel, levee and overbank complex in an ancient deep-water slope environment - Cronin, BT; Hurst, A; Celik, H; Türkmen, I (Elsevier Science Bv, 2000)
Excellent exposure of a deep-water channel-fill, levee and associated overbank sediments is described from an Eocene-Oligocene unstable slope environment. The exposure allows direct observation of spatial and temporal relationships between successive channel-fills and the channel margin. Levees are finer grained than adjacent channel-fills and temporally unrelated to them. Once formed, the levee has acted as a channel margin although not actively growing. Overbank deposits onlap the levee and can be correlated with a post-levee formation channel-fill. Direct observation of sedimentary facies relationships shows that published levee characteristics do not necessarily apply and should be applied with caution in any example where inference of spatial and temporal relationships is necessary. Levees represent the depositional elements formed during low sedimentation rates, possible periods of abandonment, with the highest preservation potential. Identification of levees is thus of importance when reconstructing the stratigraphy of sand-rich turbidite systems. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: deep-water channel; levee; overbank; Turkey